Noble Metals Doping in Lead‐Free Double Perovskite Single Crystals: Achieving Near‐Infrared to X‐ray Broadband Photodetection - Donato Valli; Roel Vanden Brande; Vincent Herreman; Qianrui Li; Giacomo Romolini; Jim Jui‐Kai Chen; Muhammed Shameem K. M.; Bob Van Hout; Li Sun; Qing Zhao; Bapi Pradhan; Johan Hofkens; et al. (Small Science)
Semiconductor materials capable of broadband photodetection, spanning X‐rays to near‐infrared (NIR), are essential for applications in medical imaging, industrial inspection, security, and telecommunications. Conventional photodetectors like Si, Ge, InGaAs, and amorphous Se (a‐Se) often encounter tradeoffs in efficiency or cost‐effectiveness. Halide perovskites (HPs) offer competitive or superior optoelectronic properties with low‐cost, solution‐based processing. However, lead‐based HPs pose toxicity and stability challenges, while lead‐free tin‐based HPs suffer from Sn2+ oxidation and structural degradation. The lead‐free double perovskite Cs2AgBiBr6 has emerged as a stable, nontoxic alternative for X‐ray and visible‐light photodetection. Despite its advantages, its high bandgap (≈1.9 eV) limits NIR absorption. This study explores doping Cs2AgBiBr6 with noble metal cations (Au3+, Pd2+, and Ir3+) to lower its absorption onset and enhance its photodetection capabilities across a broad spectrum. The results demonstrate that noble metal doping can overcome the intrinsic limitations of pristine Cs2AgBiBr6, enabling efficient photodetection from X‐rays to the NIR range. This approach highlights a viable pathway for developing next‐generation broadband photodetectors that combine nontoxicity, stability, and wide‐spectrum sensitivity.